Atmospheric reactivity of nitrate radicals: Reaction with peroxy radicals. (October 2018) - Kalalian, C.; Roth, E.; Chakir, A.
Abstract: The rate constants of the reaction of nitrate and methoxymethyl peroxy, acetonyl peroxy and β-hydroxy (methyl)propylperoxy radicals were measured using laser photolysis coupled with time resolved UV–Visible spectrometry and laser diode spectroscopy over the temperature range 276–356 K, for pressures varying between 280 and 480 Torr and was performed under dry conditions. This work provides the first kinetic data for the reaction of NO3  + CH3 OCH2 O2, NO3  + CH3 C(O)CH2 O2 and NO3  + (CH3 )2 C(OH)CH2 O2 as a function of temperature leading to the following Arrhenius expressions (in cm 3 molecule −1 s −1 ): CH3 OCH2 O2  + NO3 : k1 (T) = (1.36 ± 0.70) × 10 −11 exp (-(435 ± 150/T)) CH3 C(O)CH2 O2  + NO3 : k2 (T) = (5.47 ± 1.66) × 10 −12 exp (-(282 ± 95/T)) (CH3 )2 C(OH)CH2 O2  + NO3 : k3 (T) = (1.60 ± 1.27) × 10 −11 exp (-(480 ± 255/T)) These reactions between NO3 and RO2 radicals exhibit a low positive temperature dependence over the temperature range 276–356 K indicating that the initiation step involved in the reaction between RO2 and NO3 is carried out without an activation barrier. The effect of the peroxy radical structure on the kinetic of its reaction with nitrate radicals is relatively low. We also provide a brief discussion concerning the contribution of this process on the atmospheric elimination of RO2 in the atmosphere. Graphical abstract: Image 1 Highlights: This work provides the kinetic reaction of NO3 radicals with several peroxy radicals. Two optical detection systems are used to follow simultaneously the reactant concentrations. Temperature-dependent rate coefficients were determined in the range of 276–358 K. The effect of the peroxy radical structure on the kinetic reaction is evaluated.